2023
DOI: 10.1021/acs.langmuir.3c00885
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly, In Vitro Gene Transfection, and Antimicrobial Activity of Biodegradable Cationic Bolaamphiphiles

Abstract: Bolaamphiphiles or bolaforms have drawn particular interest in drug and gene delivery, and studies of bolaforms have been growing continuously. Bolaforms, due to their unique structure, exhibit specific self-assembly behavior in water. The present work aims to develop biodegradable cationic bolaforms with a better gene transfection ability. In this work, a novel cationic bolaform (Bola-1) with head groups bearing hydroxyl (OH) functionality was designed and synthesized to investigate self-assembly and gene tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 73 publications
0
1
0
Order By: Relevance
“…Recently, our group has demonstrated that a bolaform having urea (−NH­(CO)­NH−) linkages connecting a 6-carbon spacer chain and cationic head groups bearing hydroxyl functionalities has a promising gene transfection efficiency that is similar to the turbofectamine standard . The urea (−NH­(CO)­NH−) bond is a combination of two amide bonds where both of them may participate in a 3-way hydrogen bonding interaction with the nearby bolaform molecules .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, our group has demonstrated that a bolaform having urea (−NH­(CO)­NH−) linkages connecting a 6-carbon spacer chain and cationic head groups bearing hydroxyl functionalities has a promising gene transfection efficiency that is similar to the turbofectamine standard . The urea (−NH­(CO)­NH−) bond is a combination of two amide bonds where both of them may participate in a 3-way hydrogen bonding interaction with the nearby bolaform molecules .…”
Section: Introductionmentioning
confidence: 99%